Design a contract! : A simple principal-agent problem as a classroom experiment - Simon Gächter; Manfred Königstein (Universität Erfurt, Staatswissenschaftliche Fakultät, 2006)
We present a simple classroom principal-agent experiment that can effectively be used as a teaching device to introduce important concepts of organizational economics and contracting. In a first part, students take the role of a principal and design a contract that consists of a fixed payment and an incentive component. In the second part, students take the role of agents and decide on an effort level. The experiment can be used to introduce students to the concepts of efficiency, incentive compatibility, outside options and participation constraints, the Coase theorem, and fairness and reciprocity in contracting.
Keywords: C92; A22; 330; Classroom experiments; post-contractual opportunism; incentive contracts; efficiency; reciprocity; Coase theorem